Questioning Strategy Used by EFL Teacher in Teaching Descriptive Text at State Junior High School - Siti Frastiwi; Sabat, Yuliyanto; Aisyah, Siti (JET ADI BUANA, 2022)
Specifically, the purpose of this study to determine what types of questions teachers ask when they are teaching descriptive text. A single-case study was conducted for the purpose of this analysis. SMPN 1 Wonoayu's class VIII-I, which had ten students and one EFL instructor, participated in this study. Observation and interview were the instruments used in this study. Analysis of instructor use questioning strategy in descriptive text on classroom teaching and learning process; analysis of teacher interview statements; and analysis of student interview statements comprised three sections of the findings. An important goal was to get a better understanding of how teachers approach teaching descriptive literature, why they choose this kind of inquiry, and how students respond to the questions they are asked. It was designed to help students remember what they had learned in the previous session, and to get the class started off on the right foot. Lecture-based questioning was utilized to keep students engaged and ensure they understood what was being spoken. In order to assist students to develop their ideas, only thinking-based questions were utilized in this course. Lecture-based questions were utilized in the classroom to keep students engaged and to ensure that they understood the material. That the teacher used questioning strategies because she thought that talking with her students would make it easier to teach descriptive text, and that the students thought the teacher was good at using questioning in the classroom can be found out.